On the dynamic response of an instrumented headform for alternative mounting stiffnesses when subjected to ballistic impacts - Stone, B. W.; Harland, A. R.; Jones, J. A.; Mitchell, S. R.; Sherratt, P. J.; Ranson, C. A.; Halkon, B. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
The current British Standard for head protectors for cricketers has been recently revised to include a projectile-based battery of tests, the intention being to ensure that a certified helmet will also prevent contact of the ball or grille with the specified headform facial region. The purpose of this study was to characterise the dynamic response of the headform to direct ballistic impacts for alternative headform mounting arrangements. On one hand, and in accordance with the relevant sections of the Standard, what might be described as a `Constrained` setup was evaluated while, on the other hand, an arrangement with significantly reduced stiffness, in line with that previously reported for the passive human neck, was subject to equivalent appraisal. For each mounting scenario, an air cannon was used to project a cricket training ball at three speeds towards the instrumented headform at three locations with five repeats per speed/location combination. High-rate/resolution video and piezoelectric accelerometer data were collected and processed to determine the headform response. While differences between specific ball impact speed and location scenarios are set out in detail later in the article, overall observations are summarised as follows. From a ball/headform contact duration standpoint, video derived results showed ranges of 1.30-1.45?ms (Constrained) versus 1.26-1.41?ms. Maximum ball deformations, the timing of which enabling the event to be subdivided into `loading` and `unloading` phases, were found to be 82.5%-86.2% (Constrained) versus 82.8%-86.4% of original ball diameter; mean peak headform accelerations during loading were found to be 860-1615?m/s2 (Constrained) versus 967-1638?m/s2; and headform speeds at the end of the loading phase were found to be 0.5-0.92?m/s (Constrained) versus 0.54-0.93?m/s. Differences between headform response for the two mounting arrangements were observed to be more substantial during the loading rather than unloading phase.